A novel approach of reapplication of carbon black recovered from waste tyre pyrolysis to rubber composites. (20th January 2021) - Tian, Xiaolong; Zhuang, Qianxiao; Han, Shuang; Li, Shaoming; Liu, Haichao; Li, Lin; Zhang, Jinxiu; Wang, Chuansheng; Bian, Huiguang
Abstract: Waste tires aggravates the two major international problems of energy supply and environmental pollution in the world. Pyrolysis can convert wasted tire to valuable fuel resources, has become attractive technology. Pyrolysis carbon black (CBp) is the main secondary product of the pyrolysis of waste tires, accounting for about 35%. The high value application of CBp is one of the bottlenecks in the waste tire pyrolysis industry. Generally, the properties of CBp/rubber composites cannot meet the requirements of tires because of its poor reinforcement and dispersion. Aim to solve this problem, a novel approach which is atomization dispersion and high temperature sputtering drying (ADSD method) is applied. To evaluate the ADSD method, the performances of CBp/rubber composites prepared by different processing methods were investigated. Experimental results revealed that the performance of CBp/rubber composites prepared by ADSD method is better than that by the traditional method in terms of vulcanization performance, physical and mechanical performance, dynamic performance, etc. The feasibility of preparing rubber composites by using CBp is also verified. Graphical abstract: Image 1 Highlights: A approach for reapplication of carbon black recovered from waste tires pyrolysis (CBp) to composites. A combination of atomization dispersion and high sputtering temperature drying synergistic treatment. The feasibility of preparing composites by using CBp is verified.